Evaluation of HTLV-1 in Human Subgingival Plaque of Seropositive Patients - N. Sargolzaee; HR. Arab; A. Moeintaghavi; M. Radvar (Tehran University of Medical Sciences, 2008)
Objective: The aim of this study was to investigate the existence of human T-lymphotropic virus type 1 (HTLV-1) in subgingival plaque of HTLV-1 seropositive pa-tients. Materials and Methods: A total of 18 patients including 13 females and fivemales, with a mean age of 37 years participated in this descriptive study. Half of them were HTLV-1 carriers and the others were in HTLV-1 associated myelopathy tropical spastic paraparesia (HAM/TSP) stage.Subgingival dental plaque samples were taken using sterile paper points and examined to detect HTLV-1 using polymerase chain reaction (PCR). Results: None of the carrier stage patients revealed HTLV-1 virus, while only one patient in the HAM/TSP group was found with the virus. Conclusion: This study showed that the existence of HTLV-1 virus in subgingival plaque of patients suffering from HTLV-1 in carrier and HAM/TSP stages with healthy periodon-tium is rare. Studies with larger samples are recommended.